2021
DOI: 10.1016/j.isci.2021.102507
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone (RU486) inhibits dietary lipid digestion by antagonizing the role of glucocorticoid receptor on lipase transcription

Abstract: Lipid digestion and absorption are tightly regulated to cope with metabolic demands among tissues. How these processes are coordinated is not well characterized. Here, we found that mifepristone (RU486) prevents lipid digestion both in flies and mice. In flies, RU486 administration suppresses lipid digestion by transcriptional downregulating Magro in guts. Similarly, intestinal lipid uptake in mice was also suppressed by RU486 through the glucocorticoid receptor (GR). Further studies showed that the pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…In addition, mifepristone partially rescued the negative life span effects of a high-fat diet (HFD) in both virgin and mated females [ 27 ]. Finally, mifepristone was reported to reduce lipid uptake in flies of undefined sex [ 41 ]. Etomoxir is an irreversible inhibitor of carnitine palmitoyltransferase I (CPT I), the rate-limiting enzyme for transport of long-chain FAs into the mitochondria [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, mifepristone partially rescued the negative life span effects of a high-fat diet (HFD) in both virgin and mated females [ 27 ]. Finally, mifepristone was reported to reduce lipid uptake in flies of undefined sex [ 41 ]. Etomoxir is an irreversible inhibitor of carnitine palmitoyltransferase I (CPT I), the rate-limiting enzyme for transport of long-chain FAs into the mitochondria [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Feeding 200 μM RU486, the concentration frequently used for adult flies, caused higher developmental lethality even for the control flies in our laboratory conditions. RU486 is known to have side-effects on the physiology and lifespan of flies, depending on various factors, such as sex, mating, diet, genetic background and dose of the drug ( Landis et al, 2015 ; Ma et al, 2021 ; Robles-Murguia et al, 2019 ; Yamada et al, 2017 ). Therefore, we optimised the dosage carefully by checking the control animals.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that mifepristone does not act by direct inhibition of SREBP activation, however the reduction in size of midgut tissue expressing SREBP may still be a contributing factor to the life span increase caused by mifepristone in mated females. Recently, Ma et al reported that mifepristone inhibited Estrogen-related receptor (ERR) reporter activity in adult Drosophila , and reduced lipid content and magro lipase gene expression in the adult midgut, suggesting the possibility that ERR might be a mifepristone target ( Ma et al, 2021 ). However, fly sex was not defined in that study, so it is not clear if the observed effects occurred in males or females, or might reflect variation in the ratio of male and female flies in the samples.…”
Section: Discussionmentioning
confidence: 99%